2016
DOI: 10.1063/1.4950947
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature thermoelectric properties of the β-As2−xBixTe3 solid solution

Abstract: International audienceBi2Te3-based compounds are a well-known class of outstanding thermoelectric materials. β-As2Te3, another member of this family, exhibits promising thermoelectric properties around 400 K when appropriately doped. Herein, we investigate the high-temperature thermoelectric properties of the β-As2−xBixTe3 solid solution. Powder X-ray diffraction and scanning electron microscopy experiments showed that a solid solution only exists up to x = 0.035. We found that substituting Bi for As has a ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…Moreover for β-As 2 Te 3 it has experimentally been observed that there is a temperature dependence of the thermal conductivity, for which κ L decreases monotonically with increasing temperature, following roughly a T −1 power law. Such a feature suggests that Umklapp scattering events dominate the thermal transport in this temperature range [19,20]. The κ L values at room temperature, measured in the parallel direction were found to be low, of the order of 0.5 Wm −1 K −1 , however higher than the value obtained in the present calculations at 0.5 GPa.…”
Section: Lattice Thermal Conductivitycontrasting
confidence: 71%
See 3 more Smart Citations
“…Moreover for β-As 2 Te 3 it has experimentally been observed that there is a temperature dependence of the thermal conductivity, for which κ L decreases monotonically with increasing temperature, following roughly a T −1 power law. Such a feature suggests that Umklapp scattering events dominate the thermal transport in this temperature range [19,20]. The κ L values at room temperature, measured in the parallel direction were found to be low, of the order of 0.5 Wm −1 K −1 , however higher than the value obtained in the present calculations at 0.5 GPa.…”
Section: Lattice Thermal Conductivitycontrasting
confidence: 71%
“…Since the tetradymite structure is stable at room conditions, as demonstrated by several experimental studies performed for this compound [10,11,13,[19][20][21]56], we infer that the instability observed at 0 GPa, and located at the Z point, appears because we do not consider the anharmonic effects for the lattice-dynamics calculations. By including the anharmonic contributions, the rhombohedral structure of As 2 Te 3 at 0 GPa would probably tend to stabilize, thus suggesting that these effects can be very important for this compound, namely at the low pressure regime.…”
Section: Symmetry Groupmentioning
confidence: 92%
See 2 more Smart Citations
“…The different behaviors observed between the crystalline and composite compounds may then be explained by the different actual compositions of the phases crystallized from the glassy matrix and synthesized separately. As in Bi 2 Te 3 , small deviations from the ideal stoichiometry in both α-As 2 Te 3 and β-As 2 Te 3 are present and strongly affect the thermoelectric properties through variations in the carrier concentration. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%